Gonadal Differentiation and Development in the Snouted Treefrog, Scinax fuscovarius (Amphibia, Anura, Hylidae) - Goldberg, Francisco Javier (2015)
Accurate descriptions of gonadogenesis are necessary to have a baseline to detect abnormalities during development and to assess the time a species may be more vulnerable to the action of pesticides, endocrine disruptors, and pharmaceuticals to which abnormal conditions have been attributed. Here, I describe the histomorphological changes during gonadal differentiation in the Snouted Treefrog Scinax fuscovarius. I sexed and measured a total of 302 tadpoles between Gosner stages 26–46 and 21 juvenile and adults. The results show that 1) the species possesses the undifferentiated type of gonadal differentiation—ovaries differentiate much earlier (at stage 26) than testes (stage 36); 2) oogenesis begins almost simultaneously with ovarian differentiation; and 3) ovaries and testes exhibit different rates of gonadal differentiation with respect to somatic development—the ovaries have an accelerated rate (the ovarian cavity differentiates early during larval development and previtellogenic oocytes develop at early premetamorphic stages), whereas the testes have a decelerated rate (seminiferous tubules differentiate at the juvenile stage). The comparison of these characteristics with those of other co-occurring anuran species reveals important interspecific variation in the relative timing of gonadogenesis. Finally, and as a byproduct of the extensive sampling, I describe several cases of gonadal malformations.